Cutaneous metastasis as a breast carcinoma presentation. A case report - Daymi Martínez Rodríguez; Elizabet Fernández López; Susana Graciela Hernández Delgado (Medisur)
There are numerous skin signs and symptoms that may occur underlying the appearance of an internal neoplasia. Skin metastases from a breast neoplasm usually appear late during the progression of the disease; however, although rare, they sometimes precede this situation. The case of a patient diagnosed with cutaneous metastasis of a lobular breast carcinoma is presented, where the skin lesions were the starting point for more conclusive studies and the neoplastic diagnosis. This case is presentation due to the need to highlight the importance of the differential diagnosis that the dermatologist must perform, given the real possibility of metastatic skin lesions, in patients who consult with unusual skin lesions.